Effect of water pH different values on activity of some digestive enzymes in carp (Cyprinus carpio L.) - A.N. Nevalyonny; V.F. Zaitsev; S.N. Yegorov; S.G. Korostelyov (Acta Ichthyologica et Piscatoria, 1991)
Data cancerning the effect of evironmental pH low values on the activity of intestine carbohydrases of carp (Cyprinus carpio L.) fingerlings are given in the research. It is shown that the character of activity changes because of the hydrogen ions concentrations is analogous for all the studied enzymes. As for the physiological range of environmental pH values the activity level of the enzymes doesn′t differ or some what lower than that of the control group of fish (pH - 7.0), by the significant increase of hydrogen ions concentration the level of carbohydrases activity grows. By pathological values (pH 3) of the α-amylaseand maltase activity do not change while the saccharase and total carbohydrase activities decrease.